Learning Styles as Predictors of Academic Performance of Physics Students in Secondary Schools of Katsina Zonal Education Quality Assurance, Katsina State, Nigeria - Yahaya, Abdulkadir; Sunusi , Mamman; Mannir, Adamu Rawayau (Kashere Journal of Education, 2025)
This study investigated field dependence and field independence learning styles as predictors of students’ academic performance in Physics in secondary schools of Katsina Zonal Education Quality Assurance, katsina State, Nigeria. The study was guided by three objectives, one research question and two null hypotheses at 0.05 level of significance. The study employed Ex-Post Facto Research Design. The Population of the study comprised 5,445 SS II students from 23 Public Secondary Schools under Katsina Zonal Education Quality Assurance, out of which 357were selected as the sample of the study using proportionate sampling technique. Data was collected using two instruments: Leuven’s Embedded Figures test; with original reliability coefficients of 0.80 for the L-EFT and established coefficients of 0.89. The research question was answered using descriptive statistics (mean and standard deviation as well as frequency bar chart); while the null hypotheses were tested using linear regression analysis. Linear regression coefficients indicate low positive association between field dependence and field independence academic performance of students in physics. Hence, field dependence and field independence learning styles could not significantly predict physics performance. The researcher concludes that field dependence learning style is the most prevalent learning style whereas field independence and field dependence learning styles could not predict academic performance in Physics. Based on the findings of the study, it was recommended among others that field dependent learners should be allowed to pursue physics at secondary level of education just as field independent learners.